2013
DOI: 10.1530/edm-13-0008
|View full text |Cite
|
Sign up to set email alerts
|

Methimazole-induced myositis: a case report and review of the literature

Abstract: SummaryMethimazole is an anti-thyroid drug commonly used to treat hyperthyroidism and is a relatively safe medication. Several side effects have been reported and usually develop within 3 months of therapy. Well-known adverse reactions include agranulocytosis, hepatitis, skin eruptions, and musculoskeletal complaints such as myalgia, arthralgia, and arthritis. So far, myositis secondary to carbimazole was described in the context of a lupus-like syndrome or other rare cases of anti-neutrophil cytoplasmic antib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
10
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 3 publications
1
10
0
Order By: Relevance
“…Our patient exhibited myalgia, an extremely rare complication of both of the oral anti-thyroid treatments, 21,22 which vanished after stopping the treatment. The normal clinical and blood test results after disappearance of the muscle pain prevented us from hypothesizing as to the underlying mechanisms.…”
Section: Discussionmentioning
confidence: 74%
“…Our patient exhibited myalgia, an extremely rare complication of both of the oral anti-thyroid treatments, 21,22 which vanished after stopping the treatment. The normal clinical and blood test results after disappearance of the muscle pain prevented us from hypothesizing as to the underlying mechanisms.…”
Section: Discussionmentioning
confidence: 74%
“…Skeletal muscle constitutes a significant proportion of our body mass and relies on thyroid hormone for optimum development, function, and regeneration ( 1 , 2 , 3 , 4 , 5 ). Thyroid dysregulation, unsurprisingly, can lead to myopathic symptoms and altered basal muscle metabolism ( 1 , 2 , 3 , 4 , 5 , 6 ).…”
Section: Introductionmentioning
confidence: 99%
“…Skeletal muscle constitutes a significant proportion of our body mass and relies on thyroid hormone for optimum development, function, and regeneration ( 1 , 2 , 3 , 4 , 5 ). Thyroid dysregulation, unsurprisingly, can lead to myopathic symptoms and altered basal muscle metabolism ( 1 , 2 , 3 , 4 , 5 , 6 ). While musculoskeletal complaints are common in thyroid disorders, skeletal muscle is also vulnerable to the circulating ATD used to combat these disorders ( 1 , 2 , 4 ).…”
Section: Introductionmentioning
confidence: 99%
“…Authors speculated that the acute decrease of thyroid hormones in tissues following a state of chronic hyperthyroidism may result in relative hypothyroid states and subsequent alterations in CK concentrations as Suzuki et al mentioned before [7]. Khalil et al reported a case of MMI-induced myositis that resolved after withdrawal of the offending drug [8]. Chieh-Hua Lu described 2 cases presented with complaints of myalgia and muscle cramps, and serum CK elevation a few weeks after initiation of antithyroid treatment.…”
mentioning
confidence: 99%